Eksplorasi Masa Sejarah Khulafaur Rasyidin Sebagai Penerus Rasulullah SAW - Maulidia Ilham; Yuliastutik Yuliastutik (Departement of Mathematics Education, 2024)
Khulafaur Rasyidin is a person who has intelligence, courage, and is responsible for managing the country as the Prophet's successor as leader. Khulafaur Rasyidin was not far from being a close friend of the Prophet, including Abu Bakar Ash-Shidiq, Umar Bin Khattab. Ustman Bin Affan, and Ali Bin Ani Talib. This research uses a qualitative method with a descriptive approach using library research techniques. The aim of this research is to understand and explore the history of Khulfaur Rasyidin's time which includes leadership and educational concepts during Khulafaur Rasyidin's time. The results of this research are that Khulafaur Rasyidin means the successor of Rasulullah as leader. The process for determining who has the right to be the leader of all Khlaifahs is the same using the results of deliberation, except for Caliph Umar who was appointed directly by Abu Bakr before he died. The concept of education during Khulafaur Rasyidin's time was no different from the teachings that had been taught and implemented by the Prophet. The Caliphs used corners of the mosque for learning activities and chose Companions to become teachers. During the reign of Caliph Ustman, he made a policy that teachers were allowed to teach in any area they wanted. This concept of education was finally hampered during the time of Caliph Ali bin Abi Talib, because he was focused on suppressing political rebellions so that the concept of education was not paid attention to.